Investigating the sexual function and its associated factors in women with chronic illnesses. Issue 23 (8th October 2013) - Mollaoğlu, Mukadder; Tuncay, Fatma Özkan; Fertelli, Tülay K
Abstract : Aims and objectives: To evaluate sexual dysfunction and the factors that affect sexual dysfunction in women with chronic disease. Background: Sexual dysfunction is one of the most common problems in women with chronic disease. There is limited understanding of the related factors of sexual dysfunction in women with chronic disease, with research currently limited to other problems and problems related to chronic diseases. Design: This research was conducted as a descriptive survey. Methods: This study involved 100 female inpatients at clinics of internal medicine of a university hospital. Data were collected with a patients identification form and a female sexual function index (KCFI). Kruskal–Wallis test, test of significance of difference between two means and test of significance of difference between two pairs were used in the data analysis. Results: Sixty‐five percentage of women in the sample were defined to have sexual dysfunction. The majority of women expressed pain during sexual intercourse, problems in orgasm and satisfaction, and reluctance to have sex. Older age, being unemployed, being in menopause, fatigue, sleep disorder, and pain and weakness in extremities were the factors that were found to significantly affect the prevalence of sexual dysfunction ( p  < 0·05). Conclusions: This study concluded that sexual function of women with chronic disease is affected negatively. Chronic disease–related symptoms, experienced changes in the body and psychosocial problems are changing the lives of women. Ultimately, these changes also affect sexual activity. Relevance to clinical practice: Determination of the factors affecting sexual activity in women with chronic disease is important for women' ability to cope with sexual dysfunction and keep it under control. To be able to accomplish this, it is necessary for healthcare personnel, the partners and family to work together.